The Anthropocene on Planet Water. Competing Views on Rivers and Geography in Sergei Zalygin's Ekologicheskii roman. (2nd January 2020) - Perkiömäki, Mika
ABSTRACT: Sergei Zalygin's (1913–2000) autobiographical Ekologicheskii roman ('An Environmental Novel', 1993) tells the story of a Soviet water engineer and ecologist Nikolai Golubev between the Russian Civil War and the aftermath of the Chernobyl nuclear disaster. The protagonist is repeatedly confronted with state modernization efforts, especially on issues related to harnessing major rivers. My paper examines from an ecocritical point of view how the conflicts and dialogues between the government representatives and the main character relate to the development of Russian environmental thinking. I argue that the protagonist's relationship with his environment follows Lev Berg's almost Schellingian concept of geographical landscapes, while the state authorities typically represent Andrei Grigor'ev's ideas, based on dialectical materialism and the Stalinist interpretation of Engels's dialectics of nature. The failure to understand the significance of Vladimir Vernadskii's concept of the noosphere, the precursor of the Anthropocene, is central in the novel's critique of the Soviet state's so-called amelioration of the natural environment.